ChemInform Abstract: Convenient Synthesis of Heterocyclic Compounds with Dihydropyrano[3, 4‐b]pyridine Scaffold. Issue 29 (1st July 2013) - Pacquelet, Sandrine; Blache, Yves; Kimny, Tan; Lacaille Dubois, Marie‐Aleth; Desbois, Nicolas
Abstract: Formation of new synthesized compounds is achieved by a Polonovski rearrangement of N‐oxide derivatives followed by a Williamson′s ether synthesis.